Women in Political Party Recruitment in Japan: A Comparative Study of the Liberal Democratic Party (LDP) and the Constitutional Democratic Party (CDP) - Ulfa Azis, Ardhana (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research will shed light on the role of women in political parties in Japan. Japanis still in 125th position out of 146 countries in the World Economic Forum's Global Gender Gap Index (GGI) Report 2023. This puts Japan at the bottom among developed countries. Even though various policies related to gender equality have been taken by the Japanese government. Politics as an instrument of democracy should ideally play a role in the promotion and campaign of gender equality in Japan.  The ruling LDP  (Liberal Democratic Party) and the opposition CDP (Constitutional Democratic Party) also played the issue  of gender equality as part of efforts to respond to women's public. The response of political parties can certainly be traced to how political parties recruit and place women in party and parliamentary structures. This is the purpose of this study, to find out how the LDP and CDP recruit and candidacy women in their respective parties as an effort to realize gender equality. Using qualitative methods and party recruitment perspectives, it was found that both LDP and CDP provide space for women's involvement in their political parties. Although the LDP in the recruitment of women still uses a conservative and exclusive approach, the CDP is more progressive and inclusive. And also both, the LDP and CDP both consider the capital and political motivations of each female candidate. However, neither of them has made the affirmative quota policy effective within his party